THE REGULATION OF INTERNATIONAL LABOR MIGRATION IN REGIONAL INTEGRATION AGREEMENTS (Вісник: Міжнародні відносини, 2024)
The globalization of world economic relations is one of the main trends of our time, which not only affects the economic life, but also has deep political and social consequences. It leads to dynamic development of international integration, which is an integral part of international economic relations, along with global capital, commodity, labor and technology transfer markets. Deeper integration at the regional level established institutional distribution platform for multilateral cooperation. Intensification of regional and multilateral liberalization of trade in services is carried out by transformation not only of the basic economic relations between countries, but also between institutions that define the matrix behavior of economic agents. One of the sign of economic integration is the liberalization of labor movement in order to combine the resources and efforts of countries in solving issues of internal integration cooperation in the field of regulating labor migration flows. There are many barriers in the field of international labor movement, including migration flows within the framework of integration associations. Therefore, the central focus of this research in terms of increased regionalization of the world economy, it becomes precisely the analysis of the principles and tools of institutional regulation of labor migration in integration associations, its evolution, as well as a comprehensive assessment of economic and social consequences of this process. The key issue of institutional regulation of international labor migration in regional integration associations is the optimization of regional and global level of cooperation based on WTO rules and principles.
Keywords: global economy, international trade in services, regional trade agreements (RTA), movement of production factors , WTO, GATS, liberalization of global trade in services